Chocolate spot disease of Eucalyptus - Ratchadawan Cheewangkoon (2018)
Chocolate Spot leaf disease of Eucalyptus is associated with several Heteroconium-like species of hyphomycetes that resemble Heteroconium s. str. in morphology. They differ, however, in their ecology, with the former being plant pathogenic, while Heteroconium s. str. is a genus of sooty moulds. Results of molecular analyses, inferred from DNA sequences of the large subunit (LSU) and internal transcribed spacers (ITS) region of nrDNA, delineated four Heteroconium-like species on Eucalyptus, namely H. eucalypti, H. kleinziense, Alysidiella parasitica, and one isolate resembling a novel species in a clade separate from the holotype of Heteroconium, H. citharexyli. Based on molecular phylogeny, morphology and ecology, the Heteroconium-like species associated with Chocolate Spot disease are reclassified in the genus Alysidiella, which is shown to have mycelium that is immersed in and superficial on the host tissue and conidiogenous cells that can have loci that are either inconspicuous or proliferating percurrently. Furthermore, conidiogenous cells can either occur solitary on hyphae, or be sporodochial, arranged on a weakly developed stroma, which further distinguishes Alysidiella from Heteroconium. © 2010 The Author(s).